Deformation and Numerical Analysis of Deep Foundation Pit Under Water-Rich Ground Fissure - Kai Qin; Gang Liang; Bing-Hui Wang; Yan-Hong Li (Advances in Civil Engineering)
According to the special geotechnical problems encountered in the excavation of deep foundation pit, how to optimize the water stop and deformation scheme needs to be further studied. Taking the deep foundation pit project of Huzhu Road in Beilin District, Xi’an city, as an example, the paper analyzes the groundwater seepage and surface displacement change of the anchor pile support in the deep foundation pit, and the support scheme of local rotary jet + anchor pull pile is put forward. The results show that the uneven settlement value shows the shape of “Z,” and the maximum deformation value is about 48.2% compared than the ground fracture condition. Under the supporting scheme of + anchor row pile with local rotating jet, the hydraulic connection between inside and outside the foundation pit is reduced, which effectively makes the effective stress increase of the soil in the ground fissure area is controlled. Compared with the original measures, the maximum subsidence value on the surface is reduced by about 13.4 mm. With the new measure of foundation pit excavation, the deformation of the maximum pile body is reduced by about 19.4% compared with the original working condition, and the overall stability of the supporting structure is improved. In the aspects of supporting structure deformation, groundwater seepage, and surrounding surface settlement under the special geological conditions, the local rotary pile is better than the traditional dewatering pile anchor scheme.